2019
DOI: 10.3390/w11040711
|View full text |Cite
|
Sign up to set email alerts
|

FLIAT, An Object-Relational GIS Tool for Flood Impact Assessment in Flanders, Belgium

Abstract: Floods can cause damage to transportation and energy infrastructure, disrupt the delivery of services, and take a toll on public health, sometimes even causing significant loss of life. Although scientists widely stress the compelling need for resilience against extreme events under a changing climate, tools for dealing with expected hazards lag behind. Not only does the socio-economic, ecologic and cultural impact of floods need to be considered, but the potential disruption of a society with regard to priori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
0
8
0
1
Order By: Relevance
“…According to the review of literatures and research related to assessment of impacts and damage caused by floods using GIS and RS, it was found that there were 3 types of research, i.e., flooded area inspection [6][8-18], inspection and assessment of damage caused by floods [19][20][21][ [23][24][25][26][27][28], and the development of applications to inspect and assess damage caused by floods [23] [29]; to be described in details as follows.…”
Section: Flood Damage Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the review of literatures and research related to assessment of impacts and damage caused by floods using GIS and RS, it was found that there were 3 types of research, i.e., flooded area inspection [6][8-18], inspection and assessment of damage caused by floods [19][20][21][ [23][24][25][26][27][28], and the development of applications to inspect and assess damage caused by floods [23] [29]; to be described in details as follows.…”
Section: Flood Damage Assessmentmentioning
confidence: 99%
“…For the limitation of the research, lack of data manipulation platform made it impossible to report the results of the affected areas immediately for involved persons [24]. Van et al (2019) presented a tool to inspect impacts of floods using LULC map and socio-economic data to for damage mapping, along with analysis of the flooded areas using the data of digital elevation model, hydraulic model, and hydrologic model. The development of the tools used Python programming language.…”
Section: Flood Damage Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Berdasarkan data temuan dari hasil wawancara dan FGD, diketahui bahwa potensi bencana banjir diantaranya adalah kondisi topografi wilayah, curah hujan, dan sikap masyarakat setempat. Potensi tersebut dapat dikatakan potensi karena dapat disebabkan oleh manusia atau dampak fisik yang dapat menyebabkan hilangnya nyawa, cedera, atau dampak kesehatan lainnya, serta kerusakan dan kerugian pada properti, infrastruktur, mata pencaharian , penyediaan layanan, ekosistem dan sumber daya lingkungan (Coppola, 2011;Van Ackere, 2019). Kondisi-kondisi tersebut merupakan kondisi yang berdampak pada perubahan tata ruang atau guna lahan di suatu daerah yang kemudian menyebabkan terjadinya banjir (Rosyidie, 2013b).…”
Section: Kesadaran Guru Tentang Potensi Bencana Banjirunclassified
“…Since FLIAT (Flood Impact Assessment Tool) is a cloud computational flood impact assessment tool, it will be possible in the future to link this tool to the Internet of Floods database [209]. In contrast to desktop-based damage assessment tools, FLIAT has the advantage of using advanced parallel computation as well.…”
Section: Fliat Linked To the Internet Of Floodsmentioning
confidence: 99%